(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Perforative peritonitis is a life-threatening surgical emergency associated with high morbidity and mortality, particularly in resource-limited settings. Early risk stratification using prognostic scoring systems is essential for guiding clinical decision-making and optimizing outcomes. The Mannheim Peritonitis Index (MPI) and Jabalpur Peritonitis Index (JPI) are practical bedside tools developed for this purpose. This study aims to evaluate and compare their efficacy in predicting mortality in patients with perforative peritonitis. Methods: A hospital-based cross-sectional observational study was conducted in the Department of General Surgery at S. Nijalingappa Medical College and HSK Hospital, Bagalkot, over an 18-month period (2024–2026). Forty adult patients diagnosed with perforative peritonitis and undergoing exploratory laparotomy were enrolled. MPI and JPI scores were calculated for each patient. Statistical analysis included ROC curve analysis, chi-square tests, Student’s t-test, Mann-Whitney U test, and multivariable linear regression. Results: The cohort comprised 40 patients (75% male), median age 52.5 years. Both MPI and JPI showed significant correlation with severity parameters. MPI demonstrated greater responsiveness to clinically relevant gradients including sex, operative delay, and age. The median MPI was 25 (IQR: 20–26) and mean JPI was 6.12 ± 2.70. MPI risk classification showed 30% low, 55% moderate, and 15% high risk. Agreement between MPI and JPI risk classes was only fair (weighted kappa = 0.281), suggesting complementary rather than interchangeable utility. Conclusion: MPI demonstrated superior clinical responsiveness across severity gradients in perforative peritonitis. JPI retained utility as a simplified bedside tool, particularly in resource-limited settings. Combined use of both indices may enhance preoperative risk stratification, guide management decisions, and improve patient outcomes.